Ethics in information technology - Reynolds, George W. (America : Cengage Learning Asia Pte Ltd, 2012)
Ethics in Information Technology is a highly anticipated revision that will help readers understand the legal, ethical, and societal implications of information technology. The third edition offers updated and newsworthy coverage of issues such as file sharing, infringement of intellectual property, security risks, Internet crime, identity theft, employee surveillance, privacy, compliance, social networking, and ethics of IT corporations. This book offers an excellent foundation in ethical decision-making for current and future business managers and IT professionals.
Preface -- Chapter 1. An Overview of Ethics -- Chapter 2. Ethics for IT Workers and IT Users -- Chapter 3. Computer and Internet Crime -- Chapter 4. Privacy -- Chapter 5. Freedom of Expression -- Chapter 6. Intellectual Property -- Chapter 7. Software Development -- Chapter 8. The Impact of Information Technology on Productivity and Quality of life -- Chapter 9. Social Networking -- Chapter 10. Ethics of IT Organizations -- Appendix A. -- Appendix B.
Includes index.
Keywords: INFORMATION TECHNOLOGY -- MORAL AND ETHICAL ASPECTS